IMPLEMENTATION OF QUALITY INDICATORS IN HOSPITAL PSYCHOLOGY - Carneiro Vasconcelos, Ana Jamille; de Pontes Viana, Renata (Cadernos ESP, 2024)
This article aims to describe the process of implementing quality indicators in Hospital Psychology based on an Improvement Project. A historical series study was carried out in conjunction with quality tools to identify the problem, risks and barriers related to consultations requested in an inappropriate manner for Psychology. 40 consultations were collected per month, from March to August 2023, and the analysis framework was the “Fact-Cause-Action” methodology. The Project promoted the creation of a “Priority Matrix for Psychological Care”, an instrument that collaborated with management, assistance and health education. Two indicators were implemented, one for adherence and one for results, referring to the effectiveness of interconsultations and the response time of Psychology according to priority. An improvement in the quality and safety of the service at the institution was noticed, contributing to excellent health care.
Keywords: Health Status Indicator; Total Quality Management; Medical Psychology